Pengaruh Kegiatan Komersial Terhadap Perubahan Penggunaan Lahan di Koridor Jalan Ngesrep Timur V - Semarang - Hadi Wahyono; Yuanta Bima Andrianto (Teknik PWK (Perencanaan Wilayah Kota), 2018)
The corridor of Ngesrep Timur V Street is one of accesses to get to the education area of Diponegoro University. The corridor of Ngesrep Timur V Street became a corridor for commercial activities. Commercial activities located in the corridor of Ngesrep Timur V Street became the area center in Sumurboto Urban Village. Commercial activities in the corridor of Ngesrep Timur V Street consists of trading and service activities. The commercial activities are classified into 4 kinds: grocery store, department store, special store, and service shop. The existence of the commercial activities resulted in the rapid changes of the land use in the corridor of Ngesrep Timur V Street. The land-use change was observed from 2011 to 2017. In addition to the land-use change in the corridor of Ngesrep Timur V Street, there was the change of figure-ground from 2011 to 2017. This research aims to find out how big the influence of commercial activities towards land-use change in the corridor Ngesrep Timur V Street is. In order to achieve that objective, this research uses quantitative approach with 153 commercial activities in total. The number of the respondents in this research is 65 respondents.This research, which concerns on the effect of the commercial activities towards land-use change, is based on three main analyses namely: characteristic analysis on commercial activities, analysis on land-use change and the causes of land-use change, and analysis on the influence of commercial activities towards land-use change. This research uses index method of the closest neighbor distribution to find out the distribution pattern of the commercial activities and Chi-Square method to find out the influence of the commercial activities towards land use change. The influence of the commercial activities towards land-use change is calculated using Chi-Square value, and there are three factors which are influential such as the type of the commercial activities towards land-use change, the distribution pattern of land-use change and the cost of capital expenditure towards land-use change.